Aberration correction for hard x-ray focusing at the nanoscale - Seiboth, Frank; Schropp, Andreas; Scholz, Maria; Wittwer, Felix; Roedel, Christian; Wuensche, Martin; Ullsperger, Tobias; Nolte, Stefan; Rahomaeki, Jussi; Parfeniukas, Karolis; Giakoumidis, Stylianos; Vogt, Ulrich; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2017)
We developed a corrective phase plate that enables the correction of residual aberration in reflective, diffractive, and refractive X-ray optics. The principle is demonstrated on a stack of beryllium compound refractive lenses with a numerical aperture of 0.49 10-3 at three synchrotron radiation and x-ray free-electron laser facilities, where we corrected spherical aberration of the optical system. The phase plate improved the Strehl ratio of the optics from 0.29(7) to 0.87(5), creating a diffraction-limited, large aperture, nanofocusing optics that is radiation resistant and very compact.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Aberration correction; Compound refractive lenses; Ptychography; Wavefront sensing; X-ray optics